Political Reflection of Environmental Law Towards Regional Autonomy Law Products Holistic - Ecological Perspective - Binov Handitya; Wafda Vivid Izziyana (Universitas Muhammadiyah Gresik, 2023)
The principle of implementing a broad and intact regional autonomy that is placed on districts and cities, then Environmental Affairs are affirmed as government affairs that must be implemented by districts and cities. From the above provisions there are three important findings related to environmental management policies. First, that the region has been given the right to manage the autonomy of Natural Resources in the region, both on land and in the sea. Second, to exercise the right to regulate and take care of their own local household affairs over these natural resources, various legal products can be issued as long as they do not conflict with higher legislation or public interests. Third, the right of management of natural resources given to the region as well as followed by the responsibility of the region to preserve the environment in accordance with legislation. This research method is juridical normative. This study was conducted by examining library materials, ranging from primary legal materials, secondary legal materials and tertiary legal materials. the results of the study explain a holistic-ecological regional autonomy law product requires some fundamental changes. First, the format of granting autonomy to regions must be clear and detailed without excluding the diversity, characteristics, and capabilities of each region. Second, the scope of authority is not only